A Single-Center Retrospective Study of Bacterial Infections After Acute Ischemic Stroke: The Prevalence Before and During the COVID-19 Pandemic - Weny Rinawati; Abdulloh Machin; Aryati Aryati (Medicina)
Background and Objectives: The management of ischemic stroke involves care that is integrated and comprehensive, including the prevention of infection complications. This study aimed to investigate the prevalence and profile of bacterial infections after acute ischemic stroke both before and during the coronavirus disease 2019 (COVID-19) pandemic. Materials and Methods: A retrospective cross-sectional study examined the medical records of hospitalized acute ischemic stroke patients who had microbiological cultures taken at the National Brain Center Hospital Prof. Dr. dr. Mahar Mardjono, Jakarta, Indonesia, from 1 January 2018 to 31 December 2021. The percentage of positive bacterial growth in the microbiological cultures was used to determine the prevalence of bacterial infection after acute ischemic stroke. Results: A total of 519 patients met the study criteria, including 48 and 471 patients with infections before and during the COVID-19 pandemic. The prevalence of bacterial infection after acute ischemic stroke was 17.9%. There were significant differences in the prevalence of bacterial infection after acute ischemic stroke before and during the COVID-19 pandemic (87.5% vs. 10.8%). Staphylococcus sp. and Klebsiella sp. were the most frequently observed. The risk factors that influenced bacterial infection after acute ischemic stroke were intensive care stay (OR 0.22; 95%CI 0.13–0.39, p-value < 0.001), sepsis (OR 1.99; 95%CI 1.12–3.53, p-value = 0.019), COVID-19 infection (OR 4.81; 95%CI 2.64–8.76, p-value < 0.001), the use of steroids (OR 0.31; 95%CI 0.14–0.67, p-value = 0.003), and the use of TPN (OR 0.34; 95%CI 0.13–0.86, p-value = 0.022). Conclusions: Following the start of the COVID-19 pandemic, there was a decrease in the prevalence of bacterial infections after AIS. Patients with bacterial infections had different profiles before and during the COVID-19 pandemic.